Clinicopathologic characteristics of high expression of Bmi-1 in esophageal adenocarcinoma and squamous cell carcinoma - Choy, Bonnie (BioMed Central, 2012)
BACKGROUND: High expression of Bmi-1, a key regulatory component of the polycomb repressive complex-1, has been associated with many solid and hematologic malignancies including esophageal squamous cell carcinoma. However, little is known about the role of Bmi-1 in esophageal adenocarcinoma. The aim of this study is to investigate the amplification and high expression of Bmi-1 and the associated clinicopathologic characteristics in esophageal adenocarcinoma and squamous cell carcinoma. METHODS: The protein expression level of Bmi-1 was detected by immunohistochemistry (IHC) from tissue microarrays (TMA) constructed at the University of Rochester from using tissues accrued between 1997 and 2005. Types of tissues included adenocarcinoma, squamous cell carcinoma and precancerous lesions. Patients’ survival data, demographics, histologic diagnoses and tumor staging data were collected. The intensity (0–3) and percentage of Bmi-1 expression on TMA slides were scored by two pathologists. Genomic DNA from 116 esophageal adenocarcinoma was analyzed for copy number aberrations using Affymetrix SNP 6.0 arrays. Fisher exact tests and Kaplan-Meier methods were used to analyze data. RESULTS: By IHC, Bmi-1 was focally expressed in the basal layers of almost all esophageal squamous mucosa, which was similar to previous reports in other organs related to stem cells. High Bmi-1 expression significantly increased from squamous epithelium (7%), columnar cell metaplasia (22%), Barrett’s esophagus (22%), to low- (45%) and high-grade dysplasia (43%) and adenocarcinoma (37%). The expression level of Bmi-1 was significantly associated with esophageal adenocarcinoma differentiation. In esophageal adenocarcinoma, Bmi-1 amplification was detected by DNA microarray in a low percentage (3%). However, high Bmi-1 expression did not show an association with overall survival in both esophageal adenocarcinoma and squamous cell carcinoma. CONCLUSIONS: This study demonstrates that high expression Bmi-1 is associated with esophageal adenocarcinoma and precancerous lesions, which implies that Bmi-1 plays an important role in early carcinogenesis in esophageal adenocarcinoma.